Intellectual capital efficiency: a comparative study between Malaysian and Singaporean manufacturers / Naqiah Awang ... [et al.] - Awang, Naqiah; Hussin, Nur Syafiqah; Razali, Fatin Adilah; Abu Talib, Shafinaz Lyana (Universiti Teknologi MARA, Kedah, 2023)
Among the indicators of high business performance is Intellectual Capital (IC) efficiency. Looking at limited comparative studies on IC, this study aims to explore and compare IC efficiency and its four components among ASEAN manufacturing firms in emerging (Malaysia) and developed (Singapore) countries using a value added model. This would be a good benchmark for Malaysia since Singapore, as one of the most competitive economies in the world, can act as a role model in pursuing its innovativeness. Utilising data from annual reports of 56 manufacturing firms over three years (2012-2014), an independent sample t-test was performed. Overall, no significant difference was observed in the mean scores of Modified Value Added Intellectual Coefficient (MVAIC) and its three components (human, structural and physical capital) across both countries except for innovation capital. Thus, the current innovativeness of Malaysian manufacturers could be a basis to design and strategise appropriate mechanisms to improve IC management in becoming a developed nation as spelt in the Malaysian economic agenda. A more comprehensive measure of a firm’s IC efficiency is established by incorporating innovation capital as a standalone measure.